MORPHOLOGICAL AND NEW NEUROCHEMICAL ASPECTS OF THE MAMMALIAN CAROTID BODY - N. Lazarov; D. Atanasova (Trakia Journal of Sciences)
The carotid body (CB) is a polymodal chemosensory organ that plays an essential role in initiating respiratory and cardiovascular adjustments to maintain blood gas homeostasis. It is strategically located at the carotid bifurcation. The CB works in concert with the apposing afferent nerve endings of the petrosal ganglion (PG) cells and together they form a functional unit, the CB chemosensory system. The organ consists of small clusters called glomeruli composed of two cell types, glomus and sustentacular cells, interspersed by blood vessels and nerve bundles, and separated by connective tissue. During chemotransduction glomus cells release a variety of neurotransmitters which activate chemoafferent nerve endings of PG neurons. Much of the available evidence suggests that the CB dysfunction and altered oxygen homeostasis are involved in the pathophysiology of several diseases including systemic hypertension. Our recent data show that in glomus cells of hypertensive animals the production of nitric oxide is impaired and components of the neurotrophin signaling system display enhanced expression. These results suggest that a heightened chemosensory discharge may contribute to sympathetic hyperactivity leading to hypertension. Knowledge of the morphofunctional and neurochemical aspects of the CB would improve our current understanding of respiratory and cardiovascular homeostasis in health and disease.